Al- kharaaj bil-dhamaan put something into practice subject of book,article InheritancDoctrinal study (Islamic Sciences Journal, 2024)
ABSTRACTThe rule of “sheep in return” is a basic rule whose origin is an authentic hadith, and it has many many applications in Islamic jurisprudence, and one of the most prominent of these applications is what relates to inheritance. Therefore, I wanted to research inheritance issues with a specialized study that takes into account the jurisprudential rules and their application to inheritance issues, despite the importance of this in Scientific life, and those who are familiar with the applications of this rule in inheritance are fully aware of one of the most important rulings in which there is an increase in giving to one party of the heirs. In this research, I have relied on an explanation of the sayings of the jurists and the jurisprudence of the companions and scholars.
Keywords: Jurisprudential rule, inheritance, sheep, fines, application.